2007
DOI: 10.1128/jvi.02069-06
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the Rhesus Rhadinovirus (RRV) ORF4 Gene and the RRV Complement Control Protein It Encodes

Abstract: The diversity of viral strategies to modulate complement activation indicates that this component of the immune system has significant antiviral potential. One example is the Kaposi's sarcoma-associated herpesvirus (KSHV) complement control protein (KCP), which inhibits progression of the complement cascade. Rhesus rhadinovirus (RRV), like KSHV, is a member of the subfamily Gammaherpesvirinae and currently provides the only in vivo model of KSHV pathobiology in primates. In the present study, we characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 50 publications
(57 reference statements)
0
17
0
Order By: Relevance
“…These proteins were named RCP (6). Despite predicted high amino acid similarity between most of the proteins encoded by the two RRV strains, their RCP genes differed significantly from each other; RCP from strain 17577 (referred to as RCP-1) consists of 645 amino acids and contains eight CCP domains, whereas RCP from strain H2695 (RCP-H) consists of 395 amino acids and contains four CCP domains (18), consistent with the four CCP domains found in KCP (19). Both RCP-1 and RCP-H have a C-terminal transmembrane spanning region, as does KCP.…”
mentioning
confidence: 99%
“…These proteins were named RCP (6). Despite predicted high amino acid similarity between most of the proteins encoded by the two RRV strains, their RCP genes differed significantly from each other; RCP from strain 17577 (referred to as RCP-1) consists of 645 amino acids and contains eight CCP domains, whereas RCP from strain H2695 (RCP-H) consists of 395 amino acids and contains four CCP domains (18), consistent with the four CCP domains found in KCP (19). Both RCP-1 and RCP-H have a C-terminal transmembrane spanning region, as does KCP.…”
mentioning
confidence: 99%
“…Our group has demonstrated that the transcription program of RRV is similar to that of KSHV (17,25). Several laboratories have used the RRV model to study viral gene products, including the viral interleukin-6 homologue (37), Rta/Orf50, R8/RAP, R8.1 (17,50), R1 (13,14), R15 (46,63), RRV Orf4 (55), and the RRV-encoded microRNAs (74). We previously reported the kinetics of gene expression with regard to immediate-early, early, and late genes during RRV lytic infection and have reported that they are similar to those seen during KSHV reactivation (17,25).…”
mentioning
confidence: 99%
“…1; spliced sites indicated with a thin black bar within colored ORFs or as connections between colored ORFs). While alternate splicing has been detected in the KSHV ORF4 KCP (44) and RRV17577 ORF4 CCP (45), no conserved splice donor or acceptor sites were unambiguously identified by sequence analysis within the ORF4 homologs of the MneRV2 or RRV26-95 genomes. Additional spliced transcripts have been detected in noncoding regions of the KSHV K13, ORF72, and ORF73, but lack of sequence similarity within the MneRV2 homologs of these genes precluded the identification of conserved splice sites.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the ORF4 homolog of RRV is different in the two RRV strains. RRV26-95 encodes a protein (AAF59982) with four CCP N-terminal domains, while RRV17577 encodes a larger protein (NP_570746) with eight CCP domains (45). Analysis of the encoded amino acid sequences revealed that the MneRV2 ORF4 was closely related to the RRV26-95 and MfuRV2 ORF4 sequences with an N-terminal signal peptide, four CCP domains, and a conserved serine/threonine (S/T) domain prior to the first cysteine residue (Fig.…”
Section: Resultsmentioning
confidence: 99%